Déterminants de l'endettement extérieur des PPTE: Cas de la Côte d'Ivoire - Leonce Yapo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
In the 1980s most of Sub-Saharan African countries (SSA) especially the HIPCs faced an unprecedented indebtedness. Different mechanisms of debt relief as well as economic reforms have been put in place with the objective of enabling these countries to reach long-term economic growth and reduce their financial dependence through improvements in their external competitiveness as well as exiting from reschedulings flows cycle. Although this technical and financial assistance, in the context of IMF and World Bank supported programmes to restore financial imbalance, we notice that HIPCs continue to experience a level of debt that is unsustainable. And then, this stock of debt and debt service burdens risk worsening their social and economic development. Research on the determinants of HIPCs external indebtedness could be interesting, because of the wide consensus that durable solutions to SSA's external indebtedness may be subject to the understanding of the factors influencing indebtedness and the interactions between them.
Keywords: O11; C32; F34; O55; 330; external debt determinants; econometric model; HIPC debt relief; Côte d'Ivoire; Auslandsverschuldung; Schuldenerlass; Elfenbeinküste